A multidisciplinary approach to select junior handball players: General model - Massuca, L.; Fragoso, I. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Research on expertise or in talento identification has tended to be mono-disciplinary (Phillips et al., 2010) or focused in the inter relationships between morphologic and fitness profiles. In accordance, this study aims to evaluated: (1) the contribution of morphologic, fitness, handball-specific skill, psychological and biosocial profiles to the prediction of handball players` success; and (2) the applicability of said model to the prediction of success in junior handball players. Methods: A sample of male handball players (HB; n=225) were divided into three groups: (1) top elite (n=41); (2) non-top elite (n=126); and (3) junior elite (n=58). Morphologic, fitness, handballspecific skill, psychological and biosocial profiles were determined according to Massuça, Fragoso and Teles (in review). One logistic regression (Forward: LR) was performed, with success as dependent variable (Success=1, if the HB is a top elite athlete; Success=0, if the HB is a non-top elite athlete) and each category as predictors. Results: When the entire sample was considered, logistic regression revealed that the fitness (b=3.828, X2Wald(1)=17.180, P<.001, OR=45.978), the psychological (b=-20.343, X2Wald(1)=37.484, P<.001, OR=0.000) and the "biosocial" profiles (b=2.011, X2Wald(1)=4.986, P<.05, OR=7.471) have a significantly contribute to the prediction of success (G2(3)=106.802, P<.001; correct class. = 91.1%). This multidisciplinary model allowed us to identify 4 HB junior athletes with more than a 50% of probability of success. Discussion: It seems that fitness profile plays an important role and contributes to a great extent to high performance in handball. However, it seems that only an ideal fitness profile is not sufficient to be successful in handball. In fact, this study also showed that "biosocial" profile is also associated with handball players` success (see Massuça & Fragoso, 2010). Given the complexity of handball, it is understandable that a degree of scepticism exists as to the relevance of talent selection but, the present study investigated the relationship of a 5 categories of variables with success at a senior elite level. Furthermore, athletes are target for inclusion in development squads at a junior level therefore it is appropriate that investigations are carried out with these age groups. Moreover, our findings may provide a useful contribution to a first examination of the "Long Term Athlete Development Model" (Ford et al., 2011) in handball players.